Anti-Franco demonstration, London, 1946 (1946)
1946 1945-1960 "Anti-Franco demonstration, London, 1946" [T0489.jpg], 1946 Arthur Deakin (centre) addresses a demonstration in Trafalgar Square on 25 August, 1946. The rally, organised by the London Trades Council and supported by the TUC, demanded the immediate breaking off of diplomatic and commercial relations with Franco's Spain.